Leadership and Communication Effectiveness as Predictors of Employee Performance in MSMEs - Budi Santoso; Mohamad Iqbal Abdul Rauf; Intan Tenisia Prawita Sari (Yayasan Edukasi Cakrawala Nusantara, 2025)
This study examines the impact of leadership and communication effectiveness on employee performance in Micro, Small, and Medium Enterprises (MSMEs). Using multiple regression analysis, the findings indicate that both leadership and communication positively and significantly influence employee performance, with leadership being the strongest predictor. Together, these variables explain 61.5% of the variance in employee performance. The results emphasize the importance of effective leadership and communication within the informal and interpersonal contexts common in MSMEs. Grounded in transformational leadership theory and supported by recent studies, this research highlights the need for MSMEs to develop adaptive leadership styles and improve internal communication to enhance productivity and sustainability. The findings offer practical insights for MSME managers and policymakers focused on strengthening human capital and organizational performance, particularly in regions such as Garut.